Protocols for Establishment of Demonstration Farms in Kitui, Makueni and Taita Taveta Counties, Kenya - International Crops Research Institute for the Semi-Arid Tropics (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
A training for lead farmers and extension officers on protocols for establishing demonstration farms was conducted from 19th to 23rd September 2022 in Kitui, Makueni and Taita Taveta Counties. The purpose of this training was to equip participants with skills on how to establish demonstration farms and best options for managing drought tolerant crops in the context of conservation agriculture. The training guided in establishing demonstration plots of drought tolerant cereals and legumes grown under sole and intercropping using conservation agriculture and convectional tillage systems.